1998
DOI: 10.1002/(sici)1521-3773(19980605)37:10<1402::aid-anie1402>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Solid-Phase Synthesis of Structurally Complex Thiazolylhydantoines

Abstract: A nine-step (!) solid-phase synthesis and subsequent cleavage with cyclization from the polymeric support were the keys to preparing high-quality molecular libraries of thiazolylhydantoines 1 from modified amino acid building blocks. Each step in the synthesis is different. Because the final cyclization cleaves only molecules that have been successfully constructed, the products obtained are pure. R , R =alkyl; R =aryl, arylO; R =allyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 5 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…The attachment of thiourea groups to a solid phase is used as a precursor of guanidinium groups, as well as peptidomimetics,60 a quencher,61 thiazolylhydantoines,62 and a precursor to 2‐aminothiazole rings 63. The thiourea moiety is converted into guanidinium functionalities in the presence of different coupling reagents: N , N ‐diisopropylcarbodiimide (DIC), mercury( II ) chloride (HgCl 2 ), mercury( II ) oxide (HgO), 2‐chloro‐1‐methylpyridinium iodide (Mukaiyama’s reagent), 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide hydrochloride (EDC), 2,4‐dinitrofluorobenzene (Sanger’s reagent), and triphenylphosphane dichloride.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of thiourea groups to a solid phase is used as a precursor of guanidinium groups, as well as peptidomimetics,60 a quencher,61 thiazolylhydantoines,62 and a precursor to 2‐aminothiazole rings 63. The thiourea moiety is converted into guanidinium functionalities in the presence of different coupling reagents: N , N ‐diisopropylcarbodiimide (DIC), mercury( II ) chloride (HgCl 2 ), mercury( II ) oxide (HgO), 2‐chloro‐1‐methylpyridinium iodide (Mukaiyama’s reagent), 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide hydrochloride (EDC), 2,4‐dinitrofluorobenzene (Sanger’s reagent), and triphenylphosphane dichloride.…”
Section: Discussionmentioning
confidence: 99%
“…For a series of ethyl ester prodrugs (i.e., 3 , 5 , 6 , 8 ), protected l -ornithine 12 was prepared in two steps from commercially available 10 . First, 10 was treated with phthalic anhydride in tetrachloroethylene and then esterified under Steglich conditions with 4-DMAP, EtOH, and EDCI. , The Alloc group could then be introduced by removing the phthalimide with hydrazine and directly reacting the intermediate ornithine ethyl ester with freshly prepared allyloxycarbonyl isothiocyanate (AllocNCS, 13 ) , to furnish thiourea 14b in moderate yield (40%). Attempts to isolate the intermediate failed largely due to rapid cyclization to a δ-lactam.…”
Section: Resultsmentioning
confidence: 99%
“…Monosubstituted thiourea derivatives can be accessed through the reaction of primary amines with thiocyanates such as KSCN, NH 4 SCN 14 or coupling with benzoyl isothiocyanate followed by deprotection of benzoyl group. 15 Stadlwieser et al, 16 reported the synthesis of resin bound amino ester derived thioureas, wherein amino acid ester was treated with allyloxycarbonyl (Alloc)-isothiocyanate followed by the removal of Alloc group.…”
Section: Resultsmentioning
confidence: 99%